Implementation of Audit in Sharia Perspective - Nadia Salsabila; Mohamad Djasuli (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
Ridho Allah SWT, conveyed by the Prophet Muhammad through Islam for the good of humanity. Everything has been arranged in Islam about every line of life from the largest to the smallest. Islam also helped regulate how humans in the field of finance. Islam with a sharia base has increased interest. Companies including sharia-based financial institutions have also experienced a fairly rapid increase to date. In Indonesia, sharia -based companies are companies engaged in finance, especially banking. The operational activities of sharia -based companies do not stand alone, in the composition of capital, and their products will be related to various external parties. Based on the results of the explanation above, this article aims to analyze the implementation of audit in the perspective of sharia through the study of the results of previous studies on sharia audit practices in Indonesia. This study is a literature study research using a descriptive analysis approach. Discussion on the implementation of competency and the role of sharia auditors in Indonesia. From the discussion above it can be concluded, that the implementation of audit can be carried out but constrained in terms of quantity as well as the quality of sharia auditors in Indonesia.